PENGGUNAAN GAYA BAHASA NOVEL ANAK RANTAU KARYA A.FAUDI DALAM MENGANALISIS HASIL BELAJAR SASTRA DI SEKOLAH - Fridayanthi, Putu Dessy (LPPM IKIP PGRI Bali, 2019)
The purpose of this study was to determine the style of language contained in the novel Anak Rantau by A. Fuadi and the use of language style in the novel Anak Rantau by A. Fuadi in analyzing the results of studying literature in school. This type of research is a qualitative study that describes a phenomenon, object or social setting contained in a narrative writing, in analyzing literary works with words, sentences and discourse. This novel was published in August 2017 by PT. Falcon, with a total of 357 pages. In addition, data was also obtained through high school textbooks, high school curriculum and also books that were purchased or borrowed from the IKIP PGRI Bali library. Information in the form of facts that will be processed or analyzed as an element of drawing conclusions in researching. The method used in this study is an informal method that is presented in the form of words. Analysis using language styles that cover lexical or diction choices. The lexical choice is in the use of regional languages, foreign languages, slang Indonesian, and figurative languages. Novel Anak Rantau by A. Fuadi and Novel Ronggeng Dukuh Paruh both study language style. Novel Anak Rantau by A. Fuadi, the language style or form that is widely used is alliteration form, which is form of consonant repetition in a word or several words. In analyzing the novel students are required to understand the story in the novel and aspects of language style that are the main focus in this research. Analyzing the contents and linguistics of a literary work like a novel can add insight to students and to assess a literary work.